CARACTERIZACIÓN FÍSICA, QUÍMICA Y BIOLÓGICA DE LAS AGUAS DE LOS RÍOS HUALLAGA, PARANAPURA Y SHANUSI EN EL ÁMBITO CORRESPONDIENTE A LA CIUDAD DE YURIMAGUAS. LORETO - Armas Napuchi, Jackie (2010)
In this study we analyzed the physical, chemical and biological Huailaga river water, and Sbanusi Paranapura in the field for Yurimaguas and its variations and relationship during the months ofrain and drought.. You analizáronlas physical, chemical and biological characteristics of water in the main colíectors Yurimaguas and its variations, and, finally determinóla spatial variation of concentrations, seasons and periods of physical parameters , chemioal and biological aspects of the Huallaga river water, and Shanusi Paranapura. It realize cinco (05) monitoring of surface waters over a period of six (06) mesescomprendidos between the months of\farch to August 2009 and four (04) monitoring ofwater ofthe four main sewers ofthe city (..\nin Quebrada, Quebrada Zamora, quebrada Aguarniro and stay. Michuyacu) in December 2009. The river water was sampled on the basis of 20 parameters (pH, temperature, turbidity, dissolved oxygen, conductivity, total dissolved solids, arsenic, copper, cadrnium, chrornium, iron. manganese, mercury, lead, zinc, oils and Fats, TPH, fecal coliforms, total coliforms and E. Coli). The valúes obtained laborat ory were compared with the Standard Environmental Qualíty Waters (ECAS) approved by Supreme Decree N ° 002-2008-iMINAM and according to the dassification to which belongs each river according ResolucióriacionJefatural No. 0291-ANA